Kepemimpinan Pendidikan dalam Layanan Pembelajaran di SD Negeri 1 Widoropayung - Situbondo - Layli Rohmatillah; Hefniy; Misbahul Arifin (Education Research Center, 2025)
Educational leadership plays a strategic role in improving the quality of learning services in primary schools. This study aims to describe and analyze the role of educational leadership in the development of learning products and services at SD Negeri 1 Widoropayung, Situbondo. A qualitative descriptive approach was employed, involving the principal, teachers, and educational staff as research participants. Data were collected through classroom and school activity observations, semi-structured interviews, and document analysis, and were analyzed narratively by identifying themes, patterns, and relationships among findings. Data credibility was ensured through source and method triangulation. The results reveal that the principal implements a visionary, collaborative, and participatory leadership style in driving instructional innovation. Leadership strategies are manifested through in-house teacher training, developmental instructional supervision, provision of supporting facilities, and recognition of teachers’ creativity. Such leadership encourages the creation of various innovative learning products, including visual teaching media, literacy modules, creative lesson plans, and simple digital learning materials, as well as the development of holistic learning services addressing students’ academic, emotional, and social needs. The impact of these initiatives is evident in increased student learning motivation, enhanced teacher creativity, and the establishment of an active, inclusive, and supportive learning environment. This study concludes that strong and empowering educational leadership is a key determinant in improving the quality of learning services in primary education.